PENYULUHAN BAHAYA RADIASI PADA ANAK DI DUSUN BIBORO - Asnaeni Ansar (Lembaga Penelitian Dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2022)
The use of gadgets not only has a positive impact but also has a negative impact. Community service activities are carried out in Biboro Hamlet, Kec. Biring Bulu with counseling about the dangers of radiation to children. This counseling is held with the aim of providing knowledge to the community and determining the actions to be taken regarding themselves, namely preventing the effects of radiation on children. The implementation of counseling activities was carried out in 2 stages, namely the first stage of health counseling and the second stage followed by health checks for the residents of Dusun Biboro, Kec. Feather Birth. In the first stage, the extension material was delivered using lecture, discussion and question and answer methods. In the second stage, the health examination was carried out by PKN Muhammadiyah Muhammadiyah Makassar Health Polytechnic students. This activity succeeded in conducting outreach to 59 residents of Dusun Biboro, Kec. Feather Birth. The implementation of the activity went smoothly, full of enthusiasm from the counseling participants. The role of parents is very important in setting limits and controlling gadget play time to optimize children's growth and development